From Promise to Paranoia: A Post-Colonial Critique of Immigrants' Narratives of the American Dream - Syed Muhammad; Bahramand Shah; Abbas Jan (DIROSAT: Journal of Education, Social Sciences & Humanities, 2025)
Before 9/11, immigrants envisioned America as a land of opportunity, upward mobility, and personal freedom. The article contends that the American Dream, long romanticized as a reward for merit and hard work, is a fragile and exclusionary myth when subjected to racially fueled challenges. It argues that the 9/11 incident fundamentally disrupted the idealized notion of the American Dream for Muslim immigrants, as reflected in Laila Halaby’s Once in a Promised Land and H.M. Naqvi’s Home Boy. However, employing Homi K. Bhabha’s post-colonial concepts of hybridity, mimicry, and third space, alongside Edward Said’s theory of Orientalism, it examines how the characters’ identities become contested, fractured, and alienated in a post-9/11 context, as the then US government had passed several acts, including the Patriot Act (2001) and Homeland Security Act (2002). The sudden shift from inclusion to suspicion and from aspiration to alienation reveals a deep-rooted Orientalist gaze that constructs Muslim immigrants as the ‘Other’, dangerous, and incompatible with Western ideals. Through close textual analysis and comparative analysis, the research demonstrates how both novels dismantle the illusion of a universal American Dream and expose its conditional accessibility. Last, the paper discusses the changing dynamics of the Incumbent Trump administration's policies towards Immigrants.